ANALISIS PENGGOLONGAN KESADARAN POLITIK DALAM PARTISIPASI MASYARAKAT PADA PEMILIHAN WALIKOTA DAN WAKIL WALIKOTA DUMAI TAHUN 2015 DI KECAMATAN SUNGAI SEMBILAN KOTA DUMAI - Purnama, Keni Megawati; ', Zahirman; Erlinda, Sri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study was done to see the classification of political consciousness of community participation. The issues raised from this researchÂ  is the classification of political consciousness of community participation in the election of mayor and deputy mayor dumai 2015 in nine cities dumai river districts. This study aims to determine the classification of political consciousness of community participation in the election of mayor and deputy mayor dumai 2015 in nine cities dumai river districts. Populatuon in this study were all nine river district community are included in the permanent electoral list (DPT) for the elections in 2015 as many as 20.374 people. The sample size is determined by the technique according to the technique Sugiyono sampling area. In the first phase determines the sample area with 50% of the number of villages at random. While in the second phase which determine the people who exist in the region by means of proportion, the number of samples from study tables Isaac and Michael provide ease of determining the number of samples based on the error rate of 1%, 5% adn 10%. With this table, researchers can directly determine the sample size based on population and the error rate in wills. This study samples taken by 161 people. The method used is quntitative descriptive. The results showed taht the group of active participation of 60 respondents, as many as 31 respondents apathetic group, a radical militant group of 30 respondents, and the passive group of 40 respondents. Accompanied influential factor of political awareness and confidence in the goverment.Keywords: Political Awareness, Society Participation